Business Development through Economic Value Evaluation in the Rukun Makmur Tobacco Farmers Group in Jember Regency - Wijayanti, Rahma Rina; Triwidiarto, Cherry; Ardhiarisca, Oryza; Putra, Rediyanto (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
This study aims to evaluate the Rukun Makmur tobacco farmer group's business development in terms of costs, income, profits, and efficiency of tobacco farming. The data used in this study are primary and secondary. Primary data is data obtained directly from research respondents, namely tobacco farmers Rukun Makmur Jember. The number of samples of this study consisted of 40 farmers. This study's data were collected using 3 techniques, namely field surveys, interviews, and documentation. The data analysis technique in this study uses the profitability method and efficiency method. The results showed that the average amount of production costs incurred by the Rukun Makmur Farmer Group was 1.41 billion, consisting of direct costs of Rp. 972.9 million and implicit costs of Rp. 437.1 million. Furthermore, the average income earned was IDR 1,869 billion. Thus, the average profit earned during 2018 and 2019 is IDR 459 million, with an R / C ratio of 1.32. Based on these results, it can be said that the farming business has been efficient and feasible to do.